The Missing Link in Correlates of Protective Tuberculosis Immunity: Recognizing the Infected Cell - Lewinsohn, David Michael; Lewinsohn, Deborah Anne (Frontiers in Immunology, 2022)
For most vaccination studies, the assessment of vaccine-induced CD4+ and CD8+ T cells has relied upon the measurement of antigen-specific polyfunctional cells, typically using recombinant antigen or peptide pools. However, this approach leaves open the question as to whether or not these cells are responsive to the Mtb-infected cell within the context of Mtb infection and hence leaves open the possibility that a key parameter of vaccine immunogenicity may be overlooked. In this review, we discuss the case these measurements almost certainly over-estimate the capacity of both CD4+ and CD8+ T cells to recognize the Mtb-infected cell.